Pemanfaatan Video Animasi Untuk Edukasi Pendidikan Seks Pada Anak Usia Dini Di Kabupaten Bulukumba - Jusni; Siti Komariyah; Nursyahraeni Madika Rahman; Haerani; Ramlan M (JCS, 2024)
Starting from the many problems of sexual violence that have occurred in early childhood in recent years. Based on data from the Ministry of Women's Empowerment and Child Protection (PPPA), there were 11,952 cases of child violence, the majority of which were cases of sexual violence. This can be caused by children's lack of understanding regarding early sex education. So it is necessary to provide interesting early sex education using animated video media. This activity is carried out to increase children's understanding of early sex education regarding body parts that other people should not touch and to increase children's creative abilities. There are 3 stages in implementing this activity, namely: preparation, implementation and evaluation stages. The preparation stages include obtaining permits, field observations, collecting materials and preparing materials as well as coordinating with related parties. The stages of implementing the activity are watching an animated video about children who are good at taking care of themselves and holding a coloring competition and the third stage is an evaluation of pointing out body parts that should not be touched accompanied by questions and answers. As a result of this service activity, participants were active in this activity and were able to name parts of the body that should not be touched and how to avoid them.